Modelling the risk of Taenia solium exposure from pork produced in western Kenya. - Lian F Thomas; William A de Glanville; Elizabeth A J Cook; Barend M De C Bronsvoort; Ian Handel; Claire N Wamae; Samuel Kariuki; Eric M Fèvre (PLoS Neglected Tropical Diseases)
The tapeworm Taenia solium is the parasite responsible for neurocysticercosis, a neglected tropical disease of public health importance, thought to cause approximately 1/3 of epilepsy cases across endemic regions. The consumption of undercooked infected pork perpetuates the parasite's life-cycle through the establishment of adult tapeworm infections in the community. Reducing the risk associated with pork consumption in the developing world is therefore a public health priority. The aim of this study was to estimate the risk of any one pork meal in western Kenya containing a potentially infective T. solium cysticercus at the point of consumption, an aspect of the parasite transmission that has not been estimated before. To estimate this, we used a quantitative food chain risk assessment model built in the @RISK add-on to Microsoft Excel. This model indicates that any one pork meal consumed in western Kenya has a 0.006 (99% Uncertainty Interval (U.I). 0.0002-0.0164) probability of containing at least one viable T. solium cysticercus at the point of consumption and therefore being potentially infectious to humans. This equates to 22,282 (99% U.I. 622-64,134) potentially infective pork meals consumed in the course of one year within Busia District alone. This model indicates a high risk of T. solium infection associated with pork consumption in western Kenya and the work presented here can be built upon to investigate the efficacy of various mitigation strategies for this locality.